HEATH, Elaine A. Naked faith: the mystical theology of Phoebe Palmer. With an introduction of William J. Abraham. Cambridge: James Clarke & CO, 2010. 124 p. ISBN: 878-0-227-17339-8. - Renders, Helmut (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
Resenha do livro HEATH, Elaine A. Naked faith: the mythical theology of Phoebe Palmer. With an introduction of William J. Abraham. Cambridge: James Clarke & CO, 2010. [Tradução do título: Fé nua: a teologia mística de Phoebe Palmer. Com uma introdução de William J. Abraham]. 124p